2020
DOI: 10.1155/2020/8877003
|View full text |Cite
|
Sign up to set email alerts
|

High Dose of Intravenous Allogeneic Umbilical Cord-Derived Mesenchymal Stem Cells (CLV-100) Infusion Displays Better Immunomodulatory Effect among Healthy Volunteers: A Phase 1 Clinical Study

Abstract: Background. Mesenchymal stem cells (MSCs) express growth factors and other cytokines that stimulate repair and control the immune response. MSCs are also immunoprivileged with low risk of rejection. Umbilical cord-derived MSCs (UCMSCs) are particularly attractive as an off-the-shelf allogeneic treatment in emergency medical conditions. We aim to determine the safety and efficacy of intravenous allogeneic infusion of UCMSCs (CLV-100) by Cytopeutics® (Selangor, Malaysia) in healthy volunteers, and to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In a phase II clinical study, Tompkins et al [ 144 ] discovered that the therapeutic effects are limited to 100 million cells dosage as there are no significant therapeutic differences between 100 million and 200 million cells in the tested parameters. Another recent clinical trial concluded that administration of 130 million cells is more effective than the lower dosage of 65 million cells in producing immunomodulatory effects in healthy patients [ 146 ]. Therefore, it is postulated that a specific range of cell number is needed to exert the therapeutic effects and administration of excessive cells does not provide additional benefits.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…In a phase II clinical study, Tompkins et al [ 144 ] discovered that the therapeutic effects are limited to 100 million cells dosage as there are no significant therapeutic differences between 100 million and 200 million cells in the tested parameters. Another recent clinical trial concluded that administration of 130 million cells is more effective than the lower dosage of 65 million cells in producing immunomodulatory effects in healthy patients [ 146 ]. Therefore, it is postulated that a specific range of cell number is needed to exert the therapeutic effects and administration of excessive cells does not provide additional benefits.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Additionally, Chin et al continued to observe an increased level of anti-inflammatory cytokine IL-1RA in subjects from baseline up until 6 months post-MSC transfusion. However, note that the subjects were healthy and middle-aged which may contribute to the relatively long effectiveness of the treatment [ 176 ]. A possible solution to the limitation of MSC therapy is to find ways to sustain the survival of transplanted MSCs and increase the cell homing to the target sites to prolong the therapeutic effects.…”
Section: Mesenchymal Stem Cell Therapy To Reverse Aging Effects On the Immune Systemmentioning
confidence: 99%
“…Nevertheless, there are no significant therapeutic differences between 100 million and 200 million cells in the other tested parameters which brought to the question on why the therapeutic effects are limited to 100 million even though the dosage was doubled [ 138 ]. Another recent clinical trial concluded that administration of 130 million cells is more effective than the lower dosage of 65 million cells in producing immunomodulatory effects in healthy patients [ 176 ]. Therefore, it is postulated that a specific range of cell number is needed to exert the therapeutic effects and administration of excessive cells does not provide additional benefits.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…hWJMSCs have led to promising outcomes in preclinical and clinical studies due to their limited heterogeneity, ease of their isolation and culture, availability in several tissues, and ability to self-regenerate [18]. Also, compared to adult and fetal stem cells, hWJMSCs show a higher proliferation rate and minimum stimulation of immune and in ammatory systems [19]. So, they have newly emerged as an appropriate therapeutic vehicle for gene therapy and drug delivery.…”
Section: Introductionmentioning
confidence: 99%